PENGARUH MEDIA IKLAN TELEVISI TERHADAP KEPUTUSAN PEMBELIAN KARTU SELULER XL AXIATA PADA MAHASISWA S1-PENDIDIKAN TATA NIAGA FAKULTAS EKONOMI UNIVERSITAS NEGERI SURABAYA - ADHE M, CHAIRIL (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
Selection of media in advertising may influence the consumer's decision to purchase a product that will be offered. One of the media which is considered very appropriate in advertising a product that will be offered is to use the medium of television. Because the media is able to influence the value of television in the consumer with messages, frequency of exposure and appeal airing. One of them is a provider of enterprise mobile phone operators who currently ranks third in the PT. XL Axiata Tbk with the acquisition of as many as 31.4 million subscribers. Seeing this phenomenon, the researchers used a questionnaire distributed to students S1-Trade System Education Faculty of Economics, University of Surabaya, with a total sample of 55 people is based on purposive sampling technique. The results stated that the television advertising media consisting of advertising messages, the frequency of ad serving and ad attractiveness has a strong influence on purchasing decisions XL mobile card. This is evidenced by the acquisition of the correlation value of 0.617. Keywords : Media Television Advertising, Mobile Card Purchase Decision XL Axiata